ReMaterials : scaling up frugal innovation solutions - Mendonca, Valerie; Moses, Aditya C.; Sharma, Supriya (London : Indian Institute of Management, Ahmedabad, 2024)
ReMaterials was started in 2012 by Hasit Ganatra, when he realised the potential of an alternate product that could cater to the current needs of people living in slums. Slums are characterised by inadequate facilities, one of which is durable housing. Ganatra observed that metal sheets were the most commonly used roofing material in slums and the household had to adjust with leaky roofs in monsoons, high temperatures in summer and very little ventilation throughout the year. The residents of such houses were unable to pay for a concrete roof which was the only other option available in the market. Instead, they found it more affordable to undertake yearly repairs. Ganatra felt the need for an alternate roofing solution keeping affordability in mind. To achieve this, he experimented with industrial and agricultural waste for almost a year and came up with a roofing panel made from waste cardboard, which he called ‘Modroof.' The price of Modroof is almost half that of the concrete roof and it can last for about 20 years. In 2015, ReMaterials partnered with microfinance institutions, which offered housing loans for the underprivileged, to boost sales. In the beginning of 2017, ReMaterials aimed to achieve 500 installations by the year end to become profitable, but it was able to complete only 100 installations by the end of December 2017. Envisaged as a social enterprise, the dilemma before Ganatra was how to go about making ReMaterials profitable while keeping specific core areas in sight. There were multiple options available to him but he did not want to compromise on his vision or lose the freedom to experiment.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Roofs -- Maintenance and repair -- Case studies; Social entrepreneurship -- Case studies